The Modernization of the Settlers of Felda Semarak Jengka 15 in Pahang - Mamat, Mohd Zufri; Abd. Murad, Mohd Hazim Shah (Melayu: Jurnal Antarabangsa Dunia Melayu, 2014)
In discussion, modernization is often associated with changes in value, and in the Western concept of modernization it is associated with the openness of the community to accept change in thinking and the willingness to liberalize traditional values. The discourse on Malay modernization is also not insulated from touching on issues of changing values. Some people feel that traditional values do not have a place in the community's development and modernization efforts, while on the other hand preservation of traditional values is seen as essential for cultural identity and authenticity-hence leading to a dilemma. Taking the model of the modernization of rural Malays by FELDA as a case study, this paper will discuss the issue of Malay modernization by presenting a perspective based on the concept of "multiple modernities" which proposes modernization as something that can take various forms. This idea is contrary to the theory of conventional modernization by Marx, Durkheim or Weber, which considers societal modernization as having to follow the same path of change and development as in Western society. We suggest that the modernization of Malay society has taken a different form compared to the West, since no society exists in a vacuum but has its own unique structure of social institutions, which needs to be respected. Keywords: development, modernity, Malay modernization, values, attitudes, conventional modernization, multiple modernities